(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The development of the terms “synusia” and “bryocommunity” is explained. Bryophyte cover in the Ukrainian forest-steppe zone is characterized by its components and classified into the units: bryo-aggregations, bryo-coenoses, bryo-synusiae.